Nanofiber-based transforming growth factor-β3 release induces fibrochondrogenic differentiation of stem cells - Qu, Dovina; Zhu, Jennifer P.; Childs, Hannah R.; Lu, Helen H. (Acta biomaterialia, 2019)
[Display omitted] Fibrocartilage is typically found in regions subject to complex, multi-axial loads and plays a critical role in musculoskeletal function. Mesenchymal stem cell (MSC)-mediated fibrocartilage regeneration may be guided by administration of appropriate chemical and/or physical cues, such as by culturing cells on polymer nanofibers in the presence of the chondrogenic growth factor TGF-β3. However, targeted delivery and maintenance of effective local factor concentrations remain challenges for implementation of growth factor-based regeneration strategies in clinical settings. Thus, the objective of this study was to develop and optimize the bioactivity of a biomimetic nanofiber scaffold system that enables localized delivery of TGF-β3. To this end, we fabricated TGF-β3-releasing nanofiber meshes that provide sustained growth factor delivery and demonstrated their potential for guiding synovium-derived stem cell (SDSC)-mediated fibrocartilage regeneration. TGF-β3 delivery enhanced cell proliferation and synthesis of relevant fibrocartilaginous matrix in a dose-dependent manner. By designing a scaffold that eliminates the need for exogenous or systemic growth factor administration and demonstrating that fibrochondrogenesis requires a lower growth factor dose compared to previously reported, this study represents a critical step towards developing a clinical solution for regeneration of fibrocartilaginous tissues. Fibrocartilage is a tissue that plays a critical role throughout the musculoskeletal system. However, due to its limited self-healing capacity, there is a significant unmet clinical need for more effective approaches for fibrocartilage regeneration. We have developed a nanofiber-based scaffold that provides both the biomimetic physical cues, as well as localized delivery of the chemical factors needed to guide stem cell-mediated fibrocartilage formation. Specifically, methods for fabricating TGF-β3-releasing nanofibers were optimized, and scaffold-mediated TGF-β3 delivery enhanced cell proliferation and synthesis of fibrocartilaginous matrix, demonstrating for the first time, the potential for nanofiber-based TGF-β3 delivery to guide stem cell-mediated fibrocartilage regeneration. This nanoscale delivery platform represents an exciting new strategy for fibrocartilage regeneration.